The Relationship Between Environmental Sanitation and the Incidence of Diarrhea in the Working Area of Puskesmas Sentosa Baru - Selvi Dwi Rahman Nur Telaumbanua; Reni Agustina Harahap (LPPM UIKA Bogor, 2023)
In 2021, there was an increase in the incidence of diarrhea by 1,225 patients, starting from early January to December 2021. This study aims to determine the relationship between Environmental Sanitation and the incidence of diarrhea in the Puskesmas work area. This study used the cross-sectional method. The population of this study is people who live in the working area of Sentosa Baru Health Center. Sample selection using the Lameshow 1997 formula so that 96 samples were obtained. Statistical tests using chi-square with the help of computer software. The research site in the working area of Sentosa Baru Health Center was carried out in May-August 2022. Based on environmental sanitation, respondents who met the requirements for healthy latrines (16.7%) and did not meet the requirements (83.3%), good Clean Water Supply Facilities (11.5%) and poor Water Supply (88.5%), good Garbage Can Facilities (7.3%) and poor Garbage Can Facilities (92.7%), while Wastewater Management Facilities that met the requirements were as many (19.8%) and did not meet the requirements as much (80.2%). Research shows that there is a relationship between Environmental Sanitation including Healthy Latrines Provision Facilities (p-value = 0.00), there is a relationship between Clean Water Facilities and diarrhea events (p-value = 0.010), there is no relationship between Garbage Can Facilities and diarrhea events (p-value = 0.070), and there is a relationship between Wastewater Management Facilities and diarrhea events (p-value = 0.015).